Strategi Pengembangan Wisata Alternatif Mepantigan Yang Berkelanjutan - Putu Eka Wirawan; I Nyoman Gede Astina; Komang Ratih Tunjungsari; A. A. Ayu Arun Suwi Arianty; I Gusti Made Sukaarnawa (UHN IGB Sugriwa Denpasar, 2022)
Alternative tourism is a solution in overcoming various problems arising from the development of mass tourism. The pattern of tourists' motivation has now begun to shift from mass tourism (mass tourism) to alternative tourism ( alternative tourism ). One of these alternative tours is a stigmatizing culture, art, and cultural creation that combines martial arts, dance, drama, gamelan, and harmonization between flora and fauna in Pondok Mepantigan Batubulan Village, Sukawati Subdistrict, Gianyar Regency, Bali. The purpose of this study is to answer the question: (1) How the strategy of sustainable alternative tourism development in Batubulan Village, Sukawati Subdistrict, Gianyar Regency, Bali Province; and (2) Who and what role do the parties play in building a strategy to develop alternative sustainable tourism. This study is a descriptive qualitative study with data collection methods in interviews, observations, documentation, and questionnaires. The results showed that the development of sustainable alternative tourism requires four parties who play an essential role: First, the role of the community, Second, the role of the village government; the role of the private sector; and non-governmental organizations (NGOs). In addition, the pillars of sustainable alternative tourism development include Sustainable tourism destination management, Economic utilization for local communities, Cultural preservation for communities and visitors, Environmental conservation. Keywords :